Risk factors for repeated recurrence of cerebral aneurysms treated with endovascular embolization - Han, Yong-Feng; Jiang, Peng; Tian, Zhong-Bin; Chen, Xi-Heng; Liu, Jian; Wu, Zhong-Xue; Gao, Bu-Lang; Ren, Chun-Feng (Frontiers in Neurology, 2022)
Purpose To explore the risk factors of recurrence after second endovascular embolization of recurrent aneurysms and the characteristics of recurrent refractory aneurysms to help clinical decision-making. Materials and methods Forty-nine patients with recurrent aneurysms who underwent repeated embolization were retrospectively enrolled and divided into the recurrent and non-recurrent group. The risk factors of recurrence, complications and follow-up results of repeated embolization, and characteristics of recurrent refractory aneurysms were analyzed. Results Among the 49 patients with the second embolization, 5 were lost to follow-up, 9 recurred, and 35 did not. Univariate analysis showed that aneurysm size (P = 0.022), aneurysm classification (P = 0.014), and Raymond-Roy grade after the second embolization (P = 0.001) were statistically different between the two groups. Multivariate analysis demonstrated the Raymond-Roy grade as an independent risk factor for the recurrence of aneurysms after the second embolization (P = 0.042). The complication rate after the second embolization was 4%. There were five recurrent refractory aneurysms with an average aneurysm size of 23.17 ± 10.45 mm, including three giant aneurysms and two large aneurysms. To achieve complete or near-complete embolization of the recurrent refractory aneurysms, multiple treatment approaches were needed with multiple stents or flow diverting devices. Conclusion Aneurysm occlusion status after the second embolization is an independent risk factor for the recurrence of intracranial aneurysms. Compared with near-complete occlusion, complete occlusion can significantly reduce the risk of recurrence after second embolization. In order to achieve complete or near-complete occlusion, recurrent refractory aneurysms need multiple treatments with the use of multiple stents or flow diverting devices.